Analisa Pemanfaatan Daya Generator Set Sebagai Energi Listrik Cadangan Di AKN Aceh Barat - Sya'rani Denk, Teuku Mizan; Saputra, Herdian; Firnanda, Ary; Pandria, T. M. Azis; Daili, Cut; Hidayat, Afrilia (VOCATECH: Vocational Education and Technology Journal, 2024)
AbstractThe quality of electrical energy is a crucial requirement for the Akademi Komunitas Negeri (AKN) Aceh Barat. Electrical outages negatively impact performance, as equipment cannot be utilized during these times. A generator set is a machine that produces electrical energy and serves as a backup when the electrical supply from PLN is interrupted. Currently, AKN Aceh Barat has a generator set with a capacity of 7,800 watts, which is insufficient to meet the academy's power demands. The average monthly energy consumption from April to September 2024 is 5,199.83 kWh. To overcome the lack of power from the generator set, priority loads have been designated based on the importance of different rooms that facilitate essential services, ensuring that teaching and learning activities can proceed effectively. The generator's backup energy primarily supports a load of 6,290 watts, reaching an operational loading percentage of 81%. The electrical energy distribution from the generator to these priority rooms is managed through a new installation known as the Automatic Transfer Switch (ATS) panel, which activates automatically when the electrical supply from PLN is disrupted.Keywords:Power; Electrical; Distribution; Generator; EfficiencyAbstrakKualitas energi listrik menjadi kebutuhan utama bagi Akademi Komunitas Negeri Aceh Barat, pemadaman energi listrik berdampak buruk terhadap kinerja yang disebabkan peralatan tidak dapat digunakan. Generator set adalah mesin generator yang mampu menghasilkan energi listrik yang digunakan sebagai energi cadangan bila suplai energi listrik dari PLN terputus. pada AKN Aceh Barat generator set yang tersedia memiliki daya sebesar 7.800 watt dan tidak mampu memenuhi kebutuhan daya yang diperlukan oleh AKN Aceh Barat, rata-rata pemakaian beban AKN Aceh Barat dari bulan april sampai bulan September tahun 2024 mencapai 5.199,83 kWh per bulanya. Untuk mengatasi kekurangan daya dari generator set sebagai energi cadangan maka dipilih beban prioritas berdasarkan ruang prioritas yang berfungsi untuk pelayanan sehingga kegiatan belajar mengajar berjalan dengan baik. besar beban prioritas yang distribusi oleh daya generator sebagai energi cadangan sebesar 6.290 watt dengan persentase pembebanan mencapai 81%. Distribusi energi listrik dari genset ke ruang prioritas sebagai energi cadangan terhubung dengan instalasi baru yaitu panel ATS yang hidup secara automatis bila suplai energi listrik dari PLN terputus.Kata kunci:Daya; Distribusi; Listrik; Generator; Efisiensi